2002
DOI: 10.1103/physreve.65.036202
|View full text |Cite
|
Sign up to set email alerts
|

Transition from intermittency to periodicity in lag synchronization in coupled Rössler oscillators

Abstract: The dynamical and statistical behavior of lag synchronization in two coupled self-sustained chaotic Rössler oscillators is reexamined. The lack of uniqueness in the conventional characterization of lag synchronization based on the similarity function has caused much skepticism about the existence of lag synchronization. We provide an evidence that the emergence of lag synchronization is associated with the transition from on-off intermittency to a periodic structure in the laminar phase distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
48
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 33 publications
2
48
0
1
Order By: Relevance
“…Indeed, close to the threshold parameter values for which the coupled systems show synchronized dynamics, it is observed that the de-synchronization mechanism involves persistent intermittent time intervals during which the synchronized oscillations are interrupted by the non-synchronous behavior. These pre-transitional intermittencies have been described in details for the case of lag synchronization [5,6,7] and for generalized synchronization [8], and their main statistical properties (following those of the on-off intermittency) have been shown to be common to other relevant physical processes.As far as intermittency phenomena near the phase synchronization onset are concerned, two types of intermittent behavior have been observed so far [9,10,11,12], namely the type-I intermittency and the super-long laminar behavior (so called "eyelet intermittency" [13]). …”
mentioning
confidence: 99%
“…Indeed, close to the threshold parameter values for which the coupled systems show synchronized dynamics, it is observed that the de-synchronization mechanism involves persistent intermittent time intervals during which the synchronized oscillations are interrupted by the non-synchronous behavior. These pre-transitional intermittencies have been described in details for the case of lag synchronization [5,6,7] and for generalized synchronization [8], and their main statistical properties (following those of the on-off intermittency) have been shown to be common to other relevant physical processes.As far as intermittency phenomena near the phase synchronization onset are concerned, two types of intermittent behavior have been observed so far [9,10,11,12], namely the type-I intermittency and the super-long laminar behavior (so called "eyelet intermittency" [13]). …”
mentioning
confidence: 99%
“…Close to the threshold parameter value the coupled chaotic systems demonstrate synchronized dynamics most of the time, but there are time intervals during which the synchronized oscillations are interrupted by non-synchronous behavior. These pretransitional intermittencies have been described in [6,22,23] for the case of lag synchronization and in [24][25][26] for phase synchronization, respectively.Due to the existence of unifying framework of coupled chaotic oscillators synchronization one can also expect the intermitted behavior at the threshold of the generalized synchronization appearance. In this work we consider the behavior of coupled chaotic oscillators close to the coupling parameter value corresponding to the onset of generalized synchronization regime.…”
mentioning
confidence: 99%
“…In particular, the intermittent behavior is known to be revealed on the onset of GS [14,15] as well as in case of the lag [3,16,17] or phase [18][19][20] synchronization.…”
mentioning
confidence: 99%